Self-reported and objective sleep duration in patients with CKD: are they telling the same story? - Carvalho,Kalyanna S. Bezerra de (2022)
Abstract Introduction: There is disagreement between data on sleep duration obtained from questionnaires and objective measurements. Whether this is also true for individuals with CKD is unknown. Here we compared self-reported sleep duration with sleep duration obtained by actigraphy. Methods: This prospective study included adult individuals with stage 3 CKD recruited between September/2016 and February/2019. We evaluated subjective sleep duration by asking the following question: “How many hours of actual sleep did you get at night?” Results: Patients (N=34) were relatively young (51 ± 13 years). Self-reported and measured sleep duration were 7.1 ± 1.7 and 6.9 ± 1.6 hours, respectively, with no correlation between them (p=0.165). Although the mean difference between measurements was 0.21 h, the limits of agreement ranged from -3.7 to 4.1 h. Conclusion: Patients with CKD who are not on dialysis have an erroneous sleep perception. Data on sleep duration should be preferentially obtained from objective measurements in patients with CKD.